Volume‐related quantification of organic carbon content and cation exchange capacity of macropore surfaces in Bt horizons. Issue 1 (18th September 2020) - Leue, Martin; Uteau, Daniel; Peth, Stephan; Beck‐Broichsitter, Steffen; Gerke, Horst H.
Abstract: In structured soils, earthworm burrows, root channels, shrinkage cracks, and interaggregate spaces form complex macropore networks relevant for preferential transport, turnover processes, and root growth. Macropore walls are often coated with organomineral material, which determine physicochemical properties such as wettability, sorption, and the cation exchange capacity (CEC). The objective here was to identify volume‐averaged mean macropore coating properties of larger intact soil cores (∼7, 500 cm 3 ) from Bt horizons of Luvisols developed from loess and glacial till. The quantification of organic C (OC) content and CEC of macropore surfaces was based on three‐dimensional images of X‐ray computed tomography (XRCT) of 231‐μm voxel resolution and a vesselness procedure to distinguish between biopores and cracks. Macropore surface areas were combined with millimeter‐scaled data of OC contents and CEC of macropore coating material. The surface of macropores that accounted for 5.6 % (loess‐Bt) and 4.6 % (till‐Bt) of the samples' volumes represented approximately one‐third of the OC content and CEC of the bulk soil. Among the macropores, surfaces of larger biopores contributed most to OC content of the soil cores. The contribution of coated cracks and pinhole fillings to OC content was larger for the till‐Bt than for the loess‐Bt. Locally higher OC contents and CEC values emphasize the role of macropore surfaces in Bt horizons of Luvisols as geochemical hotspots and for mass exchange, especially during preferential flow and transport. Volume‐based coating properties may help improving macroscopic‐scale two‐domain flow and transport models. Core Ideas: Macropores are hotspots for biogeochemical and exchange processes in soils. Quantification of OC content and CEC along macropore surfaces in soil cores. Combination of XRCT‐based macropore surfaces morphologies with OC and CEC data. Macropore surface volumes (4–6 %) account for one‐third of the OC content and CEC. Macropore–matrix properties are crucial for modeling preferential transport.